Assessment of molecular diversity among linseed (Linum usitatissimum L.) genotypes using SSR markers: ASSESSMENT OF MOLECULAR DIVERSITY AMONG LINSEED GENOTYPES USING SSR MARKERS - RAM BALAK PRASAD NIRALA; SHWETA KUMARI; BISHUN DEO PRASAD (Journal of Oilseeds Research, 2020)
The high nutritive value of linseed increases its market demand for human nutrition, cosmetic, pharmaceutical and textile industry. However, the decreasing trends in areaunder linseed cultivation and yield stagnation necessitate its genetic improvement. SSR markers have been widely used in diversity analysis in linseed. In this study, molecular diversity analysis of 31 linseed genotypes were carried out using 18 SSR markers. Out of 18 SSR primers, 15 were polymorphic. The similarity coefficient ranged from 0.5 to 0.9. Among the 31 linseed genotypes studied, the lowest similarity coefficient was observed between GS-202 and Neelum (0.50). Clustering of linseed genotypes using UPGMA based on the similarity coefficient data derived from SSR markers, grouped 31 genotypes into two major clusters and ?sub clusters. It was evident from dendrogram that the genotypes GS-202, Neelum, H-40 and EC-1424 were the most diverse. Therefore, it is suggested that these genotypes may be used in breeding programme for improvement of linseed.